Toisto ja variaatio omaelämäkerrallisessa kerronnassa - Hynninen, Anna (Elore, 2004)
In this article, I explore the research possibilities for analyzing repetition and variation in autobiographical writing. My research material consists of a Karelian woman Maria’s biographical writings. Maria has written about her life for over twenty years to the Folklore Archives of the Finnish Literature Society and to the Archives of The National Board of Antiquities. She has written four autobiographies and there are striking variations from text to text. Here, I approach Maria’s repeated and varying autobiographical writing with the theory of performativity (identity and differences are performatively constituted in narration) and analyze intersectionality (an approach, which provides a conceptual frame for analyzing different social positions – gender, class, race, sexuality – and particularly the way those differences influence and constitute each other). In the article, I suggest three viewpoints of autobiographical narration which can be captured by reading one writer’s repetitive and varying narration. Firstly, narration is always bound to context. Secondly, the narrating subject is always diversified. And thirdly, reading several varying texts by one writer allows the researcher to perceive expressions of the writer’s agency. In this article, I explore the research possibilities for analyzing repetition and variation in autobiographical writing. My research material consists of a Karelian woman Maria’s biographical writings. Maria has written about her life for over twenty years to the Folklore Archives of the Finnish Literature Society and to the Archives of The National Board of Antiquities. She has written four autobiographies and there are striking variations from text to text. Here, I approach Maria’s repeated and varying autobiographical writing with the theory of performativity (identity and differences are performatively constituted in narration) and analyze intersectionality (an approach, which provides a conceptual frame for analyzing different social positions – gender, class, race, sexuality – and particularly the way those differences influence and constitute each other). In the article, I suggest three viewpoints of autobiographical narration which can be captured by reading one writer’s repetitive and varying narration. Firstly, narration is always bound to context. Secondly, the narrating subject is always diversified. And thirdly, reading several varying texts by one writer allows the researcher to perceive expressions of the writer’s agency.